(untitled) (MAUSAM, 1980)
It is shown that the occurrence of sea-thunderstorms in the Bay of Bengal, as observed by a radar study, is frequently associated with an increase in the integrated field intensity of atmospherics recorded over Calcutta at 10 and 20 kHz simultaneously. Some of the interesting results obtained from an analysis of the observations during June 1976 to May 1978 are reported in this paper and the results are discussed in the light of the present knowledge of sea-thunderstorms.